The role of training in raising the performance of employees and contributing to achieving the Kingdom’s Vision 2030 - Alotaibi, Amjad Mansuer Ethah (Journal of Economic, Administrative and Legal Sciences, 2022)
In her study on the role of training in raising the performance of workers, the researcher dealt with a case study on the health, education, and military sector in the Makkah region. The problem of the study was that most sectors and institutions face a major problem in the weakness of the training process for employees, and training may be limited to certain levels without others Training should cover all different levels of the organization. The study used the descriptive analytical method, and the various data were collected by the questionnaire method, and the total sample amounted to (174) distributed over different sectors in the Makkah region. The efficiency of the workers and the age group, with a positive direct relationship between the efficiency of the workers and the training courses. The most important recommendations were represented in: 1. The necessity of conducting a periodic evaluation of the training programs before and after the implementation of the training courses. 2.The necessity of motivating employees to obtain training courses in exchange for financial benefits and at different times to suit the conditions of the employees of the organization.